Influence of the Texture Configuration of Heating Surfaces Created by Laser Irradiation on the Ignition and Combustion Characteristics of Liquid Fuels; Applied Sciences; Vol. 13, iss. 1 - Orlova E. G. Evgeniya Georgievna; Glushkov D. O. Dmitry Olegovich; Abedtazehabadi A. Akram; Belyaev S. V. Savely Viktorovich; Feoktistov D. V. Dmitriy Vladimirovich (2023, 2023)
Title screen